SOSIALISASI PENGUATAN INTEGRITAS SEBAGAI SARANA MENUMBUHKAN BUDAYA ANTI KORUPSI PADA SISWA SD IT MUHAMMADIYAH RAWALO - Puji Susanti, Rini; Wartono, Wartono; Lestari, Ega; Permatasari, Lintang Ayu (LPPM Universitas Bina Bangsa, 2024)
This Community Service Activity (PKM) is in the form of Socialization of Strengthening Integrity as a Means of Fostering Anti-Corruption Culture in SD IT Muhammadiyah Rawalo Students. This service aims to provide understanding and strengthen integrity as a means of fostering an anti-corruption culture in students to become a young generation with integrity and anti-corruption. The target target in this PKM activity is 40 students in grade V of SD IT Muhammadiyah Rawalo. This PKM was carried out by the method of lectures, interactive dialogues and the TERAJANA (KPK) game. The lecture method is used to explain the concept of corruption, 9 (nine) anti-corruption values and their application in daily life. Meanwhile, the interactive dialogue and question and answer method provided an opportunity for the participants to share their experiences about anti-corruption attitudes and behaviors. The